REALISASI PENGEMBANGAN KUALITAS PEMBELAJARAN DI SEKOLAH BERSTATUS SEKOLAH PENGGERAK - Mahdayana, Dea; Hakim, Zerri Rahman; Pribadi, Reksa Adya (Jurnal Pendidikan Dasar, 2023)
Education in Indonesia declined when the Covid-19 pandemic emerged in early 2020. The emergence of Covid-19 caused many learning activities to be postponed or even eliminated. With the decline in the quality of education due to the Covid-19 pandemic, the government is making new innovations so that education in Indonesia improves again and is in line with the goals of education in Indonesia. The Indonesian Ministry of Education and Culture innovated by creating a driving school program specifically created during the Covid-19 pandemic in 2020. The aim of creating this driving school program was to improve the quality of education which had declined due to the emergence of the Covid - 19 pandemic in Indonesia. Researchers want to know more about the stages that schools go through to have driving school status, then the obstacles or challenges in implementing driving school activities or programs and implementing driving school learning activities. In the research carried out, researchers took data from schools using a qualitative descriptive method approach with interview, observation and documentation techniques. And the results obtained are that this driving school is a program in which the Ministry of Education and Culture together with the regional government work together to make the school become a driving school so that it can be used as an example or reference for schools that do not have driving school status.